Dissociation and ignition of methane hydrate when in contact with typical sources of fire hazard - Gaydukova O. S. Olga Sergeevna; Dorokhov V. V. Vadim Valerjevich; Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen